Enhancement of rat spermatozoal hyperactivation by progesterone - Yuki MIYAZAWA; Masakatsu FUJINOKI (The Society for Reproduction and Development, 2023)
Progesterone (P) is a well-known enhancer of hyperactivation which is associated with the success of in vitro fertilization (IVF). In this study, we examined whether P-enhanced hyperactivation affected IVF success in rats. When rat spermatozoa were exposed to 10, 20, and 40 ng/ml P, 20 ng/ml P enhanced hyperactivation via the membrane progesterone receptor. In addition, the enhancement of hyperactivation by 20 ng/ml P was regulated by phospholipase C, transmembrane adenylate cyclase, and protein kinase A. However, 20 ng/ml P did not affect IVF success. These results suggest that 20 ng/ml P enhances rat spermatozoal hyperactivation through non-genomic pathways. Because the concentration of P changes during the estrous cycle, it seems that rat spermatozoa are hyperactivated in response to the oviductal environment. However, the effect of 20 ng/ml P does not seem to fully capacitate spermatozoa.